2020
DOI: 10.3390/ma13030549
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion of Polymer Nanocomposites with Graphene and Graphene Derivative Nanofillers: An Overview of Recent Developments

Abstract: This review is focused on the recent developments of nanocomposite materials that combine a thermoplastic matrix with different forms of graphene or graphene oxide nanofillers. In all cases, the manufacturing method of the composite materials has been melt-processing, in particular, twin-screw extrusion, which can then be followed by injection molding. The advantages of this processing route with respect to other alternative methods will be highlighted. The results point to an increasing interest in biodegrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 117 publications
(171 reference statements)
1
50
0
Order By: Relevance
“…The covalent modification of graphene disrupts the aromatic system by transforming sp 2 carbon atoms into sp 3 -hybridized carbon atoms, which consequently reduces conductivity [ 13 , 14 ]; by contrast, non-covalent surface modifications, including π−π interactions, van der Waals forces, ionic interactions, and coordination and hydrogen bonding, allow the preservation of the sp 2 -hybridized system, which provides a conductivity advantage [ 14 , 15 , 16 ]. The most commonly used approaches for the incorporation of GnPs into the polyamide 6 matrix are melt compounding [ 16 , 17 , 18 , 19 ] and in situ polymerization [ 20 , 21 , 22 , 23 ]. Solution mixing is also used for the incorporation of GnPs into the PA6 matrix, but this approach requires the use of solvents such as formic acid for dissolving PA6 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The covalent modification of graphene disrupts the aromatic system by transforming sp 2 carbon atoms into sp 3 -hybridized carbon atoms, which consequently reduces conductivity [ 13 , 14 ]; by contrast, non-covalent surface modifications, including π−π interactions, van der Waals forces, ionic interactions, and coordination and hydrogen bonding, allow the preservation of the sp 2 -hybridized system, which provides a conductivity advantage [ 14 , 15 , 16 ]. The most commonly used approaches for the incorporation of GnPs into the polyamide 6 matrix are melt compounding [ 16 , 17 , 18 , 19 ] and in situ polymerization [ 20 , 21 , 22 , 23 ]. Solution mixing is also used for the incorporation of GnPs into the PA6 matrix, but this approach requires the use of solvents such as formic acid for dissolving PA6 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although significant scientific research focused on the production of high-performance PA6/GnP nanocomposite bulk plastic materials has been undertaken, studies of the production of fiber-forming PA6 composite material and melt-spun textile fibers are scarce. Existing research has identified a demanding challenge regarding the achievement of uniformly nanodispersed graphene to increase fiber conductivity while retaining fiber tensile properties [ 19 , 25 , 26 , 27 , 28 ]. Although melt processing is commercially more attractive in comparison to in situ polymerization, the high melt viscosity of thermoplastic PA6 limits the dispersibility of agglomerated GnP [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, a new group of additives based on graphene derivatives has attracted great attention worldwide. Due to the prominent chemical, thermal, mechanical, and electrical properties, graphene derivatives are considered excellent reinforcing fillers for polypropylene composites, which can greatly improve their electric conductivity as well as mechanical and thermal properties [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This has the most top tensile properties of 60.99 MPa, followed by the chemically treated glassbanana fiber hybrid laminates, which have a tensile property of 60.45 MPa (16) . Using the composites of nanoparticles are more strengthen than pure metals and improving mechanical and wear properties of the composites, the researches studied on the concepts of different composite materials, viz., Nano Sio 2 /PTFE (17) ,ABS/SiO 2 (18) , Graphene and Nano filleres (19) , Al-Si10-Mg alloy/sugarcane (20) .…”
Section: Introductionmentioning
confidence: 99%